Some factors related to the performance in mathematics of third year students in Jamaican post-primary schools - Isaacs, Ian A. (1974)
This study sought to examine some of the psychological and environmental variables that are related to the mathematics achievement of third-year students in Jamaican post-primary schools, in order to determine if there were any identifiable underlying factors that could be used to explain their variation in performance in mathematics. Mathematics achievement was measured by a 70-item researcher-designed instrument, similar to the Grade Nine Achievement Test in Mathematics of the Jamaican Ministry of Education. Data were also collected through other instruments administered to 546 students (200 boys, 346 girls) from 16 post-primary institutions (7 all-age, 14 junior secondary, 2 private secondary, 3 high schools), their mathematics teachers, and the principals or education officers of these teachers, during May and June 1971. Results of the data analysis revealed that: 1) mathematics achievement is significantly related to (a) English language achievement, (b) verbal mental ability, (c) non-verbal mental ability, (d) self-concept of mathematical ability, (e) attitudes to mathematics, (f) teacher assigned school grades/marks, (g) school location, (h) teacher experience, and (i) teacher effectiveness; 2) there was no significant relationship between teacher qualification and mathematics achievement; 3) there was a significant difference between the mathematical performance of subjects in the upper and lower social classes; 4) there was no significant difference between the mathematical performance of boys and girls; and 5) there was no significant difference between the mathematical performance of subjects taught by men and those taught by women. It was concluded that the environmental factors which are mainly determined by the social class of the subjects, the type of school they attend, and the degree of urbanization of the community in which they attend school, mask the variation in mathematics achievement that might be due to the cognitive abilities and academic aptitudes of these subjects. However, some of the variation in mathematics achievement could be attributed to those affective psychological characteristics of the subjects associated with their learning of mathematics
Keywords: Post primary students